Candida krusei infection presenting as a right ventricular mass in a two month old Infant - Patted Suresh; Halkati Prabhu; Yavagal Suresh; Patil Ravikant (Wolters Kluwer Medknow Publications, 2009)
The prevalence of fungal infections in newborns and small infants is on the rise consequent to the improved care and survival of preterm babies. Most of these premature infants are immunocompromised and subjected to invasive monitoring and therapy in neonatal intensive care units making them susceptible to nosocomial infections. We report a rare case of right ventricular mass secondary to candida krusei infection which was excised surgically. This article reemphasizes the importance of stringent aseptic practices in neonatal intensive care units to prevent nosocomial infections and the early use of echocardiography in neonates presenting with atypical unexplained symptoms to hasten diagnosis and facilitate timely intervention.